Exploring business performance in micro enterprises through entrepreneurial orientation / Rohana Ngah, Zarina Salleh and Zanariah Zainal Abidin - Ngah, Rohana; Salleh, Zarina; Zainal Abidin, Zanariah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Micro enterprises form most of business establishments in Malaysia. They represent more than 90 percent of such establishments in the country. Interestingly, most studies have shown that entrepreneurial orientation (EO) is an important element of entrepreneurship for micro enterprises. Hence, in the era of robustness of technology and explosion of knowledge, the role of knowledge sharing and innovation should be incorporated in investigating the performance of micro enterprises. This paper aims to explore the business performance of selected micro enterprises in Malaysia. One hundred and six micro enterprise owners took part in a survey. Partial Least Square was used to analyze the data. The results show that while entrepreneurial orientation on its own has no direct impact on business performance, the practice of knowledge sharing and innovation practices does. Entrepreneurial orientation and knowledge sharing have shown a strong impact on innovation where innovation reflects the impact of all variables on business performance. The study has also shown that knowledge sharing and innovation are being practiced actively in micro enterprises, thus providing a good platform for future research.